CAPTCHA: a solution for computer security or a problem to access/ use the web? - Vega, Omar Antonio (2014)
CAPTCHAs, which constitute the most widely used human interactive proofs (HIP), appear as a method of differentiation between human computer users and machines to provide security for information on the Internet and avoid spam, especially. Therefore, this paper makes an introductory presentation of HIPs, and then delves into CAPTCHAs, their evolution and classification, specifying their generation techniques, some of its applications and types of attacks to which they are subjected. It then discusses some implications that CAPTCHAs have had on usability/accessibility to the Internet services for human users, which leads to the question of whether they become a new problem, rather than a solution.